Desenvolvimento de eletrólitos nanocompósitos de nafion e nanocristais de celulose para uso em células eletrolíticas com membrana trocadora de prótons (PEMECs) - Aguiar, Jéssica de (2022)
Proton exchange membrane water electrolysis (PEMWE) performs the electrolysis of water to produce hydrogen, a source of clean and renewable energy. The most used commercial electrolyte in PEMWE is the Nafion membrane, a material that is expensive and difficult to recycle. The partial replacement of Nafion with cellulose nanocrystals (CNCs) can produce composite membranes can increased electrical, mechanical and biodegradability properties. In this sense, the objective of this work is to study the elaboration of nanocomposites (Nafion-CNC) aiming at developing high-performance electrolytes for application in PEMWE. In the first stage of the work, the potential of using agro-industrial residues (bagasse and sugarcane straw) to obtain CNCs via enzymatic hydrolysis was evaluated. CNCs obtained from both biomasses showed high crystallinity index (> 70%) and high thermal stability (Tonset > 300 °C). In the second stage, the effects of adding CNCs to Nafion were evaluated. Nafion membranes were produced with two types of CNCs, one obtained by enzymatic hydrolysis and the other by acid hydrolysis (commercial). The addition of both CNCs has similar effects on Nafion’s properties. For samples with both commercial and enzymatic CNC, an increase in the modulus of elasticity (10% and 40% respectively) and maximum stress (10% and 13% respectively) was observed. The two nanocomposites showedlower initial thermal degradation temperatures, however, they still showed sufficient stability (Tonset > 170°C) for application in PEMWE (standard operating temperature <100°C). Furthermore, there was a significant increase in the humidification capacity and increase in conductivity. Composite membranes were tested in PEMWE and their usability was proven.